1997
DOI: 10.1111/j.1365-2621.1997.tb15016.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of Egg White Proteins as Affected by Combined Heating and Freezing

Abstract: Combined effects of preheating (60ЊC, 0 ϳ 30 min) and freezing (Ϫ10 or Ϫ20ЊC, 20 hr) on the gelation of dried egg white induced by reheating (80ЊC, 30 min) were examined in comparison with those of refrigerating (5ЊC, 20 hr). Refrigeration consistently induced harder gels, while freezing resulted in either harder or softer gels. Results of soluble protein content, turbidity, SDS-PAGE and gel filtration indicated that the unfolded and aggregated levels of ovotransferrin, caused by the cooperative effects of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Controlled heating in dry state of egg white (for example, 80°C for 5-10 days) was found to be effective to improve significantly functionalities such as gelling, emulsifying, and foaming properties and water holding capacity without any loss in solubility (Kato et al, 1989(Kato et al, , 1990aMine, 1996Mine, , 1997. We also showed that when the solutions of spray-dried (60-70°C) and then dry-stored (55-65°C, 3 days) egg whites were reheated at 60°C for several minutes, coagulation hardly occurred (Xu et al, 1997). This phenomenon was also found to be mainly attributable to changes of the egg white proteins occurring in the process of heating in the dry state.…”
Section: Introductionmentioning
confidence: 82%
“…Controlled heating in dry state of egg white (for example, 80°C for 5-10 days) was found to be effective to improve significantly functionalities such as gelling, emulsifying, and foaming properties and water holding capacity without any loss in solubility (Kato et al, 1989(Kato et al, , 1990aMine, 1996Mine, , 1997. We also showed that when the solutions of spray-dried (60-70°C) and then dry-stored (55-65°C, 3 days) egg whites were reheated at 60°C for several minutes, coagulation hardly occurred (Xu et al, 1997). This phenomenon was also found to be mainly attributable to changes of the egg white proteins occurring in the process of heating in the dry state.…”
Section: Introductionmentioning
confidence: 82%
“…The gel sheets were stained with a solution of 0.2% Coomassie Brilliant Blue R-250 in water/methanol/acetic acid (5:5:1, v/v/v) and destained by 7% acetic acid overnight. Sodium dodecyl sulfate (SDS)-PAGE in the presence and absence of 2-mercaptoethanol (2-ME) was carried out according to the method of Laemmli (1970) as described in the previous paper (Xu et al, 1997).…”
Section: Effects Of Cacl 2 and Ph At Dry-heating On Dhew Turbidity An...mentioning
confidence: 99%
“…In a previous study (Xu et al, 1997), we showed that when solutions of spray-dried (60-70 °C) and then heattreated egg white (55-65 °C, 3 days in a dry state to reduce microbial numbers) were reheated at 60 °C for various times, the insoluble materials in their solutions almost failed to form. Such a phenomenon was also found to be mainly attributable to changes in proteins occurring in the process of heating in a dry state.…”
Section: Introductionmentioning
confidence: 96%
“…The proteins of whole blood plasma, serum and plasma fractions interacted with egg white proteins producing stronger gels (Howell & Lawrie, 1984). The aggregations of serum protein with egg white can occur during heating through the exchange reaction of sulfhydryl groups and disulfide bonds (Howell & Lawrie, 1984;Xu et al, 1997). The exchange reaction of free sulfhydryl groups of ovalbumin with disulfide bonds of serum proteins, especially serum albumin, occurred when a small quantity of egg white or ovalbumin was added to the serum and enhanced the gel strength.…”
Section: Resultsmentioning
confidence: 99%